(untitled) (Latakia University Journal -Biological Sciences Series, 2012)
جُمعت ووصفت ستة أنواع من جنس الصنوبر Pinus L. المنتشر في سوريا وهي: الصنوبر البروتيPinus brutia Ten .، الحلبيMill P.halepensis، الثمري P.pinea L.، الأسود P. pallasiana Lamp. ،الشعاعي P. radiata D.Don والصنوبر الكناريP. canariensis Sweet ek sprengel. وتمّ تحليل درجة القرابة ضمن أنواع جنس الصنوبر بالبرنامج الإحصائي (Statistica 2008)، بإدخال قاعدة بيانات شملت (162) صفة موروفولوجية للأنواع المدروسة تضمنت الفروق والتشابهات. بيّنت النتائج ارتباط الصنوبر البروتي والصنوبر الحلبي بعنقود واحد، أما الصنوبر الثمري فقد كان أقرب إلى الصنوبر الأسود، واجتمعا بعنقود واحد، واشترك معهما الصنوبر الشعاعي بفرع، ولكن النوع الأخير كان أقرب إلى الصنوبر الأسود أكثر من الصنوبر الثمري، وانفرد الصنوبر الكناري بفرع وحيد وكان الأقرب إلى الصنوبر الشعاعي. Six species of genus Pinus L, were collected and described: Pinus brutia Ten, P.halepensis Mill, P.pinea L., P. pallasiana Lamp., P. radiata D.Don, P.canariensis Sweet ek sprengel. Consanguinity among the species of Pinus L. was analyzed using (Statistica 2008) program. Data constituents were (162) morphological characteristics containing differences and similarities of studied species. Results showed that Pinus brutia Ten. and P.halepensis Mill correlated with one cluster, while P.pinea L. was closer to P. pallasiana Lamp., both having one cluster and sharing a branch with P. radiata D.Don. The last specie was closer to P. pallasiana Lamp. than P.pinea L.. P. canariensis Sweet ek sprengel had only one branch and was the closest to P.radiata D.Don .